2021
DOI: 10.1016/j.jaip.2020.11.033
|View full text |Cite
|
Sign up to set email alerts
|

What the COVID-19 Pandemic Can Teach Us About Resource Stewardship and Quality in Health Care

Abstract: The coronavirus disease 2019 pandemic has forever changed how we view health care service delivery. Although there are undoubtedly some unintended consequences that will result from current health care service reallocation, it provides a unique opportunity to consider how to deliver quality care currently, and after the pandemic. In the context of lessons learned, moving forward some of what was previously routine could remain reserved for more exceptional circumstances. To determine what is "routine," what is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Previous studies found that gender is also a risk factor for COVID-19 [ 34 , 35 ]. Abundance of gut microbiota of Female vs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that gender is also a risk factor for COVID-19 [ 34 , 35 ]. Abundance of gut microbiota of Female vs.…”
Section: Resultsmentioning
confidence: 99%
“…The approach demonstrates how we can learn from the pandemic and it supplements other ways to identify low value care. The approach is also recognized and applied in many other fields [ 39 48 ] to identify and reduce a range of low-value services.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has provided the opportunity to reconsider how healthcare quality is defined moving forward, and there are several reasons why a wait and see approach, in certain contexts, is reasonable. 68 As mentioned, during the pandemic, the most salient reason is to keep children out of the ED, both owing to healthcare resource allocation and infection risk. 67,69 However, there are other reasons to consider this option that extend beyond pandemic circumstances.…”
Section: Not All Anaphylaxis Requires Activation Of Emergency Medical...mentioning
confidence: 99%